Experimental study of DVB-T2 in Thailand - Suwansukho, Nattapan; Promwong, Sathaporn (My University, 2017)
This paper presents an analysis of digital television broadcasting, that used DVB-T2 standard, in Bangkok Thailand. The result of analysis has derived from signal measurement 20 location in Bangkok. The measurement location consists of several difference areas such as an urban area, high building area, open area. The measurement's result are consists of signal strength, C/N, MER, SNR, NsMAR, bBER, LBER, power output after combiner. The measurement illustrates the effect of attenuation and interference in propagation channel. The propose of this study is checking DVB-T2 channel characteristic approximately attenuation between transmitted antenna at base station and received antenna at far field. The result of the analysis could be useful for improve and design the digital television broadcasting network.
Keywords: BBER; DVB-T2; Experimental; Field strength